Exportación de red meat para el mercado norteamericano con fines de industrialización - Mora Bustos, Mariuxi (2014)
The present research entitled “EXPORTACIÓN DE RED MEAT PARA EL MERCADO NORTEAMERICANO CON FINES DE INDUSTRIALIZACIÓN” was design with the purpose of analyzing the economic and financial feasibility of exporting the waste generated in the production of canned tuna in Galapesca SA in order to increase the supply of exportable products. For that reason, four chapters have been developed which will focus on expanding the technical knowledge of the process of exporting a perishable product, conduct market research to position the product in the US market, improve the economic conditions of the company and therefore the country, through the export of RED MEAT and perform planning investment costs and budgets needed to establish the viability of the project……